Professional orientation and competence of future professionals with a “person ‐ person” occupational type - Kokun, Oleg M. (Social Welfare: Interdisciplinary Approach, 2012)
Year in year out researchers pay more and more attention to psychological aspects of professional development of specialists with a “person-person” occupational type. This is due to constant increase in the social signifi cance of these jobs. The paper presents the results of research aimed to determine psychological aspects of professional orientation and competence formation for future specialists with the “person-person” occupational type that can be used to improve effi ciency of their professional training.